2014
DOI: 10.2217/pmt.14.36
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Anxiety in the Transition from Acute to Chronic Pain: There is Evidence for Endurance Besides Avoidance

Abstract: Substantial evidence reveals that the fear of pain and pain anxiety play a significant role in the development of chronic pain and disability, although underlying mechanisms remain widely unknown. Recent studies indicate that endurance pain responses are important besides avoidance. The purpose of this brief narrative review is to provide an overview of research that argues for the integration of the mechanisms of associative learning, motivation and emotion regulation in order to understand the questions of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 77 publications
5
43
2
8
Order By: Relevance
“…This kind of research intriguingly corroborate clinical findings in patients with subacute or chronic pain who reported high levels of endurance behaviour in situations with severe pain, addressed at "dysfunctional endurance" [6][7][8]. Moreover, the avoidance-endurance model of pain (AEM) [9] suggests two subgroups of patients with an endurance pain response pattern, namely patients showing signs of so-called eustress versus distress endurance responses (EER vs. DER), besides a well-known fear-avoidance subgroup. DER patients have been shown higher pain-related disability, more fatigue and less positive mood than EER [8,10] while both subgroups displayed higher pain intensity than an adaptive group and higher percentage of physical activity, especially in backstrain positions [10].…”
Section: Editorialsupporting
confidence: 72%
“…This kind of research intriguingly corroborate clinical findings in patients with subacute or chronic pain who reported high levels of endurance behaviour in situations with severe pain, addressed at "dysfunctional endurance" [6][7][8]. Moreover, the avoidance-endurance model of pain (AEM) [9] suggests two subgroups of patients with an endurance pain response pattern, namely patients showing signs of so-called eustress versus distress endurance responses (EER vs. DER), besides a well-known fear-avoidance subgroup. DER patients have been shown higher pain-related disability, more fatigue and less positive mood than EER [8,10] while both subgroups displayed higher pain intensity than an adaptive group and higher percentage of physical activity, especially in backstrain positions [10].…”
Section: Editorialsupporting
confidence: 72%
“…We briefly mention one other model- the avoidance-endurance model (AEM) 85;86 , which has some overlap with the FAM, though it emphasizes the importance of particular behaviorally-defined subgroups. 87 The AEM hypothesizes that while some patients experiencing persistent pain will become fearful and activity-avoidant, others will show an “endurance response”, characterized by maintained activity and task persistence.…”
Section: Mechanism-based Pain “Models”mentioning
confidence: 99%
“…We should also note that the present article is only one in a long line of studies and classification systems that have suggested phenotyping, or clustering, patients on the basis of psychosocial characteristics, with the eventual goal of predicting treatment responses or other pain-related outcomes (e.g., disability) [24;25;45;132]. Such efforts include measurement tools such as the West Haven-Yale Multidimensional Pain Inventory (MPI, [144]), which yields empirically validated subgroups of patients [206], the Örebro Musculoskeletal Pain Screening Questionnaire [31;156], which clusters patients according to their risk for developing persistent pain, the Treatment Outcomes in Pain Survey - Short Form (S-TOPS, [117]), which phenotypes multiple physical and emotional pain-related domains, the STarT back tool, designed as a primary care screening instrument, which predicts recovery from acute back pain [124;257], as well as models such as the fear-avoidance model [59;246], and the avoidance-endurance model [120;121]. The comparison (and perhaps eventual integration) of these measures and models is unfortunately beyond the scope of the present work, but it is noteworthy that essentially all of these classification systems lean heavily on the assessment of negative affective symptoms (e.g., depression, anxiety, distress] and maladaptive pain-related cognitions [e.g., catastrophizing) [205].…”
Section: Phenotypic Domainsmentioning
confidence: 99%